Numerical investigation of the effect of weather conditions on the escalation and propagation of fire-induced domino effect - Ahmed Malik, Asher; Nasif, Mohammad Shakir; Mokhtar, Ainul Akmar; Mohd Tohir, Mohd Zahirasri (Wiley, 2021)
Fire-induced domino accidents are less probable but highly consequent. Although past studies conducted risk assessment of such events, classical models were used for impact estimation. Moreover the influence of varying weather on evolution of fire domino effect was not investigated, where past research necessitates the use of computational fluid dynamics to perform such analysis. This paper adopts a consolidated risk analysis approach to perform consequence modeling using fire dynamics simulator. Various atmospheric conditions were incorporated in the model. The outcomes were used in probabilistic analysis to estimate the escalation probabilities. Risk of domino events was presented as domino levels. It was found that 37% reduction in humidity ratio resulted in 10% decrease in tanks failure time. At 3 and 6 m/s winds, the failure time of tank in flame direction reduced by 56% and 80%, whereas the escalation probability increased by 3 and 4 orders respectively. The tank farm failed in 11.3 and 12.85 min at 3 and 6 m/s respectively, which is less than the suggested mitigation time.